(untitled) (Andamios, Revista de Investigación Social, 2013)
This paper explores the adoption of foreign concepts in Latin-American urban planning and Architecture. We ask about the reasons and the means in which city actors are taking and adapting those theories. Also we point main urban concepts shaping landscapes in XXI century. Mexico city brings us a good example of that process. The main conclusion is about the circulation of ideas with significant changes that allows partial new concepts emerge from the Latin-American reality.